Algunas Características de los Embriones Colectados de Vicuña (Vicugna vicugna) en el CIP Quimsachata del INIA PUNO - Cárdenas Minaya, Oscar Efraín; Sapana, R.; Gonzáles Castillo, Mario Lino; Mamani Cato, Rubén Herberht (Universidad Nacional del Altiplano, 2021)
4 páginas